The Statesman's Yearbook 2008 - Turner, B. author. aut Link
1600 p.
Keywords: The 2008 edition of The Statesman's Yearbook contains information and analysis on every country in the world, including biographical profiles of current leaders, government histories, economic overviews and maps. Every copy comes with a single-user licence giving access to the full text online, updated regularly and fully searchable.